Accounting Practices and Success of Business: A Survey of Traders of Muhanga Commercial Centre in Rwanda - Anastasie, Uwamahoro; Rusibana, Claude (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2020)
Some businesses start well and whereas some succeed others fail. The question is why some businesses survive while others collapse. This study, therefore, seeks to inform traders and other profit oriented activities owners of Muhanga Commercial Centre about the role of accounting system in preparing and keeping the books of accounts and the relationship between accounting system and business success or performance. The specific objectives of the study are to find out whether traders of Muhanga commercial centre keep accounting records, to establish the factors affecting growth of business, to find out the performance level of the traders in Muhanga Commercial Centre and establish the relationship between accounting practices and success of the traders. This research is of significance to business managers and scholars. Considering the methodology used in this study, a descriptive survey research design was employed in this study in order to capture the general overview giving some valuable pointers as to what variables are worth testing quantitatively and can yield rich data that lead to important recommendations in practice. The target population for this study is 292 traders of Muhanga Commercial Center and the sample size of 74 respondents. Stratified sampling was used to select the sample respondents. Sample size was determined using Slovin’s formula with 10% error margin. The qualitative and quantitative data was used. For primary data, questionnaires were sent to the respondents and interview was used. The secondary data was collected from journal articles, books and internet resources. Statistical Package for Social Sciences (SPSS) version 21.0 was used to analyse the relationship between accounting record keeping and the business success. Reliability of the instruments was established after a pre-test in order to establish the fitness of the instruments in the study. Moreover, experts in the field were consulted about the content of instruments, ambiguity of question items and their relevance. The results of the study revealed that there is a positive correlation between recording and business expansion with p- value of 0.912 and sig=.000; between financial statements and increase in asset with p-value of 0.780 and sig=.000; between reconciliation and increase in profit with a p-value of 0.884 and sig=.000; between reconciliation and financial statements with p- value of 0.674 and sig=.000; between increase in profit and recording with a p-value of 0.822 and sig=.000; between recording and financial statements with p-value of 0.615 and sig=.000; between reconciliation and recording with a p-value of 0.914 and sig=.000; between reconciliation and business expansion with a p-value 0.938 and sig=.000; increase in asset and business expansion with a p-value of .849 and sig=.000, increase in profit and business expansion with a p-value of 0.917 and sig=.000 and between financial statement and increase in profit with a p – value of 0.802 and sig=.000 because the calculated P-value is less than 0.01 level of significance.